Dialogical musical gatherings and initial teacher training: Contribution to improvement of competencies - Isusi-Fagoaga, Rosa; Fernández-Maximiano, Rafael (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This work focuses on dialogic and communicative action between people with the intention of improving their education. For this, the format of dialogical literary gatherings has been adapted to the content of musical works. The main objectives have been: to develop communicative, linguistic and musical skills through interactive dialogue; increase the degree of motivation and increase the musical culture of future teachers towards classical music. A qualitative and quantitative methodology and the research-action method are combined. The sample has been 136 students, future teachers in training. The main results offer positive data.